Hell - Huijgen, Arnold (SysLex, 2025)
Three main positions concerning hell can be distinguished. First, the Augustinian view of hell as place of eternal punishment, which stamped the Western tradition, with the variation of a purgatory (Roman-Catholic) or without it (Protestant). Second, in the Eastern tradition, universalist tendencies rendered hell a transitional phase after which all shall be saved. Third, annihilationism states that while believers live eternally, the damned are destroyed forever. Diverse interpretations of Biblical Scripture lead to a proliferation of all three options. Meanwhile, modern humanism has put the Augustinian option under pressure.